Expression of anti‐Müllerian hormone, CDKN1B, connexin 43, androgen receptor and steroidogenic enzymes in the equine cryptorchid testis. (7th January 2013) - Almeida, J.; Conley, A. J.; Ball, B. A.
Summary Reasons for performing study Cryptorchidism affects 2–8% of male horses and the affected testis undergoes a disruption of normal spermatogenesis. The underlying molecular changes are poorly understood in the cryptorchid equine testis. Objectives Compare the expression of anti‐Müllerian hormone (AMH), anti‐Müllerian hormone receptor (AMHR2), androgen receptor (AR), cyclin kinase inhibitor (CDKN1B), connexin 43 (Cx43), 3β hydroxysteroid dehydrogenase/Δ5‐Δ4‐ isomerase (3βHSD), P450c17 hydroxylase/lyase (P450c17) and cytochrome P450 aromatase (P450arom) in the undescended testis of cryptorchid stallions with that of normal stallions. Methods Undescended, abdominal testes from four cryptorchid stallions between 2 and 3 years of age were collected during routine castrations along with normally descended testes from normal stallions between 2 and 3 years of age (n = 7). Samples were analysed by immunohistochemistry and quantitative real‐time PCR. Results Cryptorchid testes had increased AMH and AMHR2 immunolabelling when compared with normal testes, which indicates failure of maturation of Sertoli cells and/or lack of testosterone suppression. Failure of Sertoli cell maturation in the cryptorchid testis may also be attributed to AR abnormalities and/or a consequence of lack of testosterone suppression due to decreased 3βHSD. Cyclin‐dependent kinase (CDKN1B) was not expressed in Sertoli cells of cryptorchid testes suggesting that Sertoli cells are still proliferating, which is also a characteristic of the immature testis. In addition, Cx43 expression is decreased in the cryptorchid testis, indicating a disruption in intercellular communication. Conclusions Undescended testes of cryptorchid horses present characteristics of immaturity suggesting that the failure of Sertoli cell maturation may be a consequence of cryptorchidism. Potential relevance This study provides a better understanding of the effect of cryptorchidism on testicular function in stallions.